Feeding Habits and Activity Patterns of Grivet Monkey (Chlorocebus aethiops L.) in Batiero Church Forest, Northern Ethiopia - Alelign, Aschalew; Yonas, Meheretu; Moges, Eshetu (International Journal of Zoology, 2023)
Grivet monkeys (Chlorocebus aethiops) are restricted to fragmented forests where food and space are limiting factors. The study investigated the feeding and activity patterns of grivet monkeys in Batiero Church Forest, northern Ethiopia, using focal and scan sampling techniques. Both focal and scan animal sessions lasted 15 min, with 5 min rest intervals between sessions. During the early dry season, grivet monkeys mainly fed on Acacia sieberiana (26.5%) and Juniperus procera (17.5%). Dry season food selection was significantly different, J. procera (20.5%), Acacia mearnsii (15.6%), A. sieberiana (14.2%), and Cyperus bulbosus (12.7%). The predominant plant parts eaten were seeds (42.6% and 33.3% in early dry and dry seasons, respectively) followed by leaves (34.5% and 22.5% in early dry and dry seasons, respectively). The activity patterns showed no significant seasonal variation, and the most frequent activity was feeding (33.3% and 32.6%, in early dry and dry seasons, respectively). The preferred food source tree species are threatened, and the survival of the grivet monkeys depends on the conservation of indigenous plants and trees.